cDNA clone encoding Drosophila transcription factor TFIID. - Muhich, M L (1990)
Proper initiation of transcription by RNA polymerase II requires the TATA-consensus-binding transcription factor TFIID. A cDNA clone encoding the Drosophila TFIID protein has been isolated and characterized. The deduced amino acid sequence reveals an open reading frame of 353 residues. The carboxyl-terminal 180 amino acids are approximately 80% identical to yeast TFIID and 88% identical to human TFIID. The amino-terminal portions of the yeast and Drosophila TFIID proteins lack appreciable homology, whereas the Drosophila and human amino termini appear qualitatively similar. In addition, the amino-terminal region of the Drosophila TFIID contains several sequence motifs that are found in other Drosophila proteins which appear to regulate transcription.